Postoperative catecholamine resistance following fetal methamphetamine exposure. (January 2019) - Perumal, Gopinath; Marathe, Supreet P; Schlapbach, Luregn J; Morwood, Jim; Venugopal, Prem; Alphonso, Nelson
Methamphetamine and its related compounds are among the most widely abused recreational drugs worldwide. While a myriad of clinical complications of methamphetamine use have been described, there is a paucity of literature regarding the effects of maternal abuse during pregnancy on neonatal hearts. In this report, we describe a neonate who underwent Norwood-type palliation and subsequently developed catecholamine-resistant cardiogenic shock, likely related to methamphetamine exposure, which recovered after a period of venoarterial extracorporeal membrane oxygenation support.